An investigation of an open‐access model for scaling up methadone maintenance treatment - Madden, Lynn M.; Farnum, Scott O.; Eggert, Kathryn F.; Quanbeck, Andrew R.; Freeman, Robert M.; Ball, Samuel A.; Schottenfeld, Richard S.; Shi, Julia M.; Savage, Mary Ellen; Barry, Declan T. (Addiction (Abingdon, England), 2018)
Aims To examine retrospectively patient and programmatic outcomes following the development and implementation of an ‘open‐access’ model in which prospective patients were enrolled rapidly in methadone maintenance treatment, irrespective of ability to pay, and provided real‐time access to multiple voluntary treatment options. Design Medical and administrative records were ed to compare data for 1 year before and 9 years after initiating the implementation of an open‐access treatment model in May 2007. Setting Methadone maintenance treatment center in Connecticut, USA. Participants Individuals with opioid use disorder entering treatment between July 2006 and June 2015. In June 2015, 64% (n = 2594) of the sample were men and 80% (n = 3133) reported that they were white. Intervention The Network for the Improvement of Addiction Treatment‐informed open‐access treatment model uses process improvement strategies to improve treatment access and capacity. Measurements Census, waiting time, retention, non‐medical opioid use, patient mortality and financial sustainability (net income and state‐block grants as proportions of revenue). Findings In the 9 years following the initial implementation of the open‐access model, patient census increased by 183% from 1431 to 4051, and average waiting‐time days decreased from 21 to 0.3 (same day) without apparent deleterious effects on rates of retention, non‐medical opioid use or mortality. Between fiscal years (FY) 06 and FY 15, net operating margin rose from 2 to 10%, while state‐block grant revenues declined 14% and the proportion of total revenue from state‐block grant revenue decreased from 49 to 24%. Conclusions An open‐access model for rapid enrolment of people with opioid use disorder in methadone treatment appears to improve treatment access, capacity, and financial sustainability without evidence of deleterious effects on treatment outcomes.